Augmented Reality (AR) in Physics Learning: Opportunities to Improve Teacher and Student Interaction in Online Learning - Nurhasanah, Siti; Abdurrahman, Abdurrahman; Andra, Doni; Herlina, Kartini (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to describe the views of teachers and students in Islamic schools regarding Augmented Reality (AR) assisted learning to facilitate student involvement in learning, as well as increase teacher-student interactions in the learning process during the Covid-19 pandemic. This study uses a mixed method with a qualitative-quantitative explanatory design. The data collection technique used a questionnaire involving 31 respondents, 3 teachers, and 3 students as resource persons in three Islamic high schools in Lampung Province. The results of the study show that AR-assisted methods have the potential to increase teacher-student interaction by implementing a Learning Management System (LMS) that suits their needs and learning facilities. The results also show that AR provides an effective learning experience, because it displays 3D images so that it is easily accepted by students and makes students interested in learning during online learning. Therefore, the use of AR in learning has the opportunity to increase learning interactions between teachers and students.